THE HISTORY OF THE POLISH-UKRAINIAN BORDERLAND AS AN IMPERATIVE FOR THE CREATIVITY OF THE LITERARY GROUP “ZIEWONIA” - Сухарєва , Світлана (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2023)
The article highlights the historical motives and inspirations of the literary group “Ziewonia”. Attention is drawn to the influence of the historical era (the period of the November Uprising of the Poles and being under Russian oppression), as well as previous milestones in Polish and Ukrainian history, which were signposts to national liberation. The peculiarities of the development of Ukrainophilism within the general Slavophilism of the first half of the 19th century are taken into account. The place of the scientific concept of Zorian Dołęga-Chodakowski on the transformation of the historical approach to the reception of Slavic literature in general, and Polish and Ukrainian in particular, is determined. In addition to the influence of famous historians, it is also worth highlighting the extraordinary role of the Society of Friends of Science in Lviv. It was from there that ideas about the transformation of historical models came in order to revive the people’s struggle and patriotic sentiments in society. Along with chronicle historicism and Walterscottism, the writers of the “Ziewonia” group in their works highlight the principles of folk historicism, which is largely based on Ukrainian folklore. Song folk images and plots, historical events from Dum are the basis of most of the poetic works of representatives of the “Ziewonia” group. Some of them have clearly expressed anti-Ottoman motives. Thus, Seweryn Goszczyński’s work “Kościelisko” was written in the spirit of folk historicism, as it depicts the struggle of the inhabitants of the Carpathian region against the Tatar army. The presence of a common enemy among the Ukrainian and Polish peoples from previous centuries is transferred to the first half of the 19th century, when such an enemy was the Russian Empire and other imperialist conquering states. Therefore, inspirations of national liberation can be found everywhere in the poetry, prose and drama of “Ziewonia”. The key in historical inspiration was the image of a folk hero or a Cossack. Slavophilic writers successfully put into practice the program principle of “Ziewonia” dedicated to history, in particular literary and critical reflections on the place of Galician writing.

У статті висвітлено історичні мотиви та інспірації творчості літературної групи “Зевонія”. Звернено увагу на вплив історичної доби (період Листопадового повстання поляків та перебування під російським гнітом), а також попередні віхи польської та української історії, які були дороговказами до національного визволення. Враховано особливості розвитку українофільства у межах загального слов’янофільського руху першої половини ХІХ століття. Визначено вплив наукової концепції Зоріана Доленги-Ходаковського на трансформацію історичного підходу до рецепції слов’янської літератури в цілому, та польської й української зокрема. Проаналізовано особливості народного історизму, який поєднував слов’янофільські мотиви польських та українських митців і вповні виразився у програмних творах “Зевонії”.
ІСТОРІЯ ПОЛЬСЬКО-УКРАЇНСЬКОГО ПОГРАНИЧЧЯ ЯК ІМПЕРАТИВ ТВОРЧОСТІ ЛІТЕРАТУРНОЇ ГРУПИ “ЗЕВОНІЯ”
Keywords: слов’янофільство; українофільство; історизм; польсько-українське пограниччя; “Зевонія”; романтизм; Slavophilism; Ukrainophilism; historicism; Ukrainian-Polish borderland; “Ziewonia”; romanticism